GAMBARAN DISIPLIN DAN PRESTASI KERJA TERHADAP PROMOSI JABATAN KARYAWAN HRD PT. TELKOM INDONESIA BANDUNG - Pranamulya, Yoga; Mulyadi, Hari; Purnama, Ridwan (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Â Purpose - The purpose of this study is to know the description of discipline, job performance and promotion positions.Design/methodology/approachh - The design of this study was cross sectional. This research uses descriptive approach with explanatory survey method. An employee analysis unit of 96 respondents. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is descriptive technique by using frequency distribution.Findings - Based on the results of the research using descriptive analysis, the results showed that the work discipline is in the category quite appropriate with the score of 75.4%, job performance in high category with score 76.9% and job promotion in the high category with score 77.9%.Originality/value - This research provides a fundamental understanding for issues of work discipline, job performance and promotion. The difference of this research with the previous research is the object of research that is studied in service sector, theory and reference used are the latest theories.Â